Uncovering incontinentia pigmenti: From DNA sequence to pathophysiology - How, Kang Nien; Leong, Hazel Jing Yi; Pramono, Zacharias Aloysius Dwi; Leong, Kin Fon; Lai, Zee Wei; Yap, Wei Hsum (Frontiers in Pediatrics, 2022)
Incontinentia pigmenti (IP) is an X-linked dominant genodermatosis. The disease is known to be caused by recurrent deletion of exons 4-10 of the Inhibitor Of Nuclear Factor Kappa B Kinase Regulatory Subunit Gamma (IKBKG) gene located at Xq28 chromosomal region which encodes for NEMO/IKKgamma, a regulatory protein involved in the nuclear factor kappa B (NF-κB) signaling pathway. NF-κB plays a prominent role in the modulation of cellular proliferation, apoptosis, and inflammation. IKBKG mutation that results in a loss-of-function or dysregulated NF-κB pathway contributes to the pathophysiology of IP. Aside from the typical skin characteristics such as blistering rash and wart-like skin growth presented in IP patients, other clinical manifestations like central nervous system (CNS) and ocular anomalies have also been detected. To date, the clinical genotype-phenotype correlation remains unclear due to its highly variable phenotypic expressivity. Thus, genetic findings remain an essential tool in diagnosing IP and understanding its genetic profile allows greater possibility for personalized treatment. IP is slowly and gradually gaining the attention in the field of research, but there is much that remains to be understood. This review highlights the progress that has been made in IP including the different types of mutations detected in various populations, current diagnostic strategies, IKBKG pathophysiology, genotype-phenotype correlation, and treatment strategies, which will provide insights into understanding this rare mendelian disorder.